2011
DOI: 10.1183/09031936.00197810
|View full text |Cite
|
Sign up to set email alerts
|

Clara cells drive eosinophil accumulation in allergic asthma

Abstract: Development of allergic asthma is a complex process involving immune, neuronal and tissue cells. In the lung, Clara cells represent a major part of the ''immunomodulatory barrier'' of the airway epithelium.To understand the contribution of these cells to the inflammatory outcome of asthma, disease development was assessed using an adjuvant-free ovalbumin model. Mice were sensitised with subcutaneous injections of 10 mg endotoxin-free ovalbumin in conjunction with naphthaleneinduced Clara cell depletion.Clara e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…CC-16 is a natural immune-regulator protecting the respiratory tract from unwanted inflammatory reactions [78]. CC-16 levels in serum increase when lung epithelium permeability is adversely affected by air pollutants or other lung toxicants.…”
Section: Discussionmentioning
confidence: 99%
“…CC-16 is a natural immune-regulator protecting the respiratory tract from unwanted inflammatory reactions [78]. CC-16 levels in serum increase when lung epithelium permeability is adversely affected by air pollutants or other lung toxicants.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Furthermore, CC also respond actively to Th2-inflammation by producing eotaxin and undergoing epidermal growth factor receptor (EGFR)-mediated mucus metaplasia. [15][16][17] Related to this, our previous findings indicated that CC mucous metaplasia leads to a marked decrease in CCSP and SP-D secretion. 18,19 In common with epithelial cells, AM are also plastic cells involved in the first line of defense against inhaled agents, which are endowed with a high phagocytic and microbicidal potential and a lower expression of MHC class II molecules.…”
Section: Introductionmentioning
confidence: 92%
“…As a consequence of exposure to the antigen, the release of eosinophils from bone marrow is mainly influenced by interleukin (IL)-5 and specific chemoattractants, such as eotaxin (Brightling, 2001). Recent investigation revealed Clara cells, important part of the “immunomodulatory barrier” of the airway epithelium, as the principal source of eotaxin in the lung (Sonar et al, 2012). It is also believed that exposure to the antigen induces trafficking of IL-5-producing T lymphocytes to the bone marrow, further promoting eosinophilopoiesis through IL-5 signaling (Gauvreau et al, 2009).…”
Section: Immune Responsementioning
confidence: 99%